Multicultural Narratives in Indonesian Education Historiography: Study Discourse-Historical Approach History Textbook of Senior High School - Sunardi, Akhmad Dwi Afiyadi, Leo Agung S dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research tries to trace the multicultural narrations produced by government throughtextbooks of history lesson (high school) as compulsory subjects. This research is based onthe theory of multiculturalism which states that multiculturalism is the recognition ofcultural diversity including ethnic, religious, racial and intergroup diversity. On the otherhand this articles attempts to look at the multicultural narrations produced by thegovernment in the textbooks of historical pursuits and the political context of education inthe production of multicultural narratives.The multicultural narratives described in the textbook of the history lessons ideally depictthe territory of Indonesia which has a diversity of tribes, religions, race and groups. Theresult of this study are expected to find whether the narrative textbooks of history lessonshave revealed historical facts that reflect the diversity of Indonesian society and see howthe political context of education, whether to position the textbook as a way of controllingthe official historical narratives that students, educators and policy makers education.Keywords: [Multicultural Narratives, History Textbook, Discourse-Historical Approach,Education Historiography]